Association between heart rate, heart rate variability, cortisol, glucose and electrolytes in healthy newborn calves - D.A.C. Quevedo; M.L.G. Lourenço; C.A.D. Bolaños; R.K. Takahira; E. Oba; A. Alfonso; S.B. Chiacchio (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2019)
ABSTRACT This study aims at evaluating the effects of electrolytes, glucose and cortisol levels over heart rate (HR) and heart rate variability (HRV) in healthy newborn calves. Seventeen healthy Holstein calves were evaluated during their first month of life, and the plasma concentrations of glucose, cortisol, calcium, magnesium, inorganic phosphorus, sodium and potassium were analyzed. HRV indexes were determined in the time and frequency domains through the analysis of neonatal electrocardiogram recordings. In the first day, low blood levels of phosphorus presented a strong correlation with the HR and the increased high-frequency components of HRV. The plasma concentrations of magnesium decreased significantly throughout the 35 days, revealing a positive association with a decreasing low-frequency components of HRV at day 28. There was a strong correlation between HR, HRV indexes, some plasma electrolytes, glucose and cortisol during the studied period. Variations in the concentrations and correlations observed may be attributed to the adaptive neonatal period in calves.